Perceived benefits and barriers to exercise and associated factors among Zimbabwean undergraduate students: a cross-sectional study - Shava, Beatrice K.; Vhudzijena, Blessed; Kupenga-Maposa, Tariro; Musingwini, Thelma; Samudzi, Tanaka; Muchemwa, Sidney; Chibanda, Dixon; Dambi, Jermaine M. (Frontiers in Sports and Active Living, 2024)
Background Despite the well-documented benefits of regular physical activity (PA), many university students are physically inactive. Personal, socio-economic, and environmental factors predict PA engagement behaviours in university students. There is a need to understand context-specific perceived barriers and benefits to exercise engagement and physical activity levels amongst university students from low-income settings. This study primarily evaluated the barriers and facilitators to PA engagement in Zimbabwean undergraduate students. We also assessed the correlates of perceived barriers and benefits to PA engagement, risk of common mental disorders (CMDs) and health-related quality of life (HRQoL). Methods We used a cross-sectional study to recruit 465 university undergraduate students. The Exercise Benefits and Barriers Scale, International Physical Activity Questionnaire (IPAQ), Shona Symptoms Questionnaire (SSQ-8) and EuroQol 5 Dimension (EQ5D-5l) were used to measure barriers and facilitators, physical activity level, risk of depression and anxiety and HRQoL, respectively. Data were analysed through descriptive statistics and logistic regression. Results and conclusion Most participants were male (58.5%) with a mean age of 21.7 (SD 1.6) years. Majority of the participants were first year students (37.2%), consumed alcohol (66.5%), did not smoke (88.2%) and had a normal BMI (64.7%). The prevalence of low PA levels was 17.4%, with 33.5% of students at risk of CMDs. The most perceived benefits were in the physical performance (e.g., exercise improves my level of physical fitness) and life enhancement (e.g., exercise improves my self-concept) domains, while the most perceived barriers were lack of exercise infrastructure (e.g., exercise facilities do not have convenient schedules) and physical exertion (e.g., exercise tires me). Food insecurity (AOR 2.51: 95% CI 1.62–3.88) and the risk of CMDs (AOR 0.49: 95% CI 0.32–0.76) were associated with increased odds of experiencing barriers to exercise. Not using substances (AOR = 2.14: 95% CI 1.11–4.14) and a higher self-rated HRQoL (AOR 24.34: 95% CI 1.77–335.13) were associated with increased odds of a high perception of exercise benefits. Improving access to community and on-campus exercise facilities and campus-wide health promotional interventions is necessary to enhance PA amongst university students.